2014
DOI: 10.1016/j.lwt.2014.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mechanical and optical properties of French fries obtained by hot air-frying

Abstract: ElsevierHeredia Gutiérrez, AB.; Castelló Gómez, ML.; Argüelles Foix, AL.; Andrés Grau, AM. (2014 The aim of this study was to analyse the influence of frying technique (air-frying and 9 deep oil-frying) and type of pre-treatment (freezing and blanching) on the evolution of 10 mechanical and optical properties of French fries. The results showed that the 11 chromatic parameters, a * and b *, experimented an increase regardless of the frying 12 method; while the increase in a * was significantly higher in deep-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 22 publications
7
22
0
4
Order By: Relevance
“…According to Heredia et al (2014) samples showed an initial stage of softening or firmness loss from the maximum value of firmness registered at time zero, followed by a second stage where maximum force tended to increase as the surface crust appeared. This crusty texture is a consequence of changes in the external layers of the product at a cellular level.…”
Section: Deep Fryingmentioning
confidence: 99%
“…According to Heredia et al (2014) samples showed an initial stage of softening or firmness loss from the maximum value of firmness registered at time zero, followed by a second stage where maximum force tended to increase as the surface crust appeared. This crusty texture is a consequence of changes in the external layers of the product at a cellular level.…”
Section: Deep Fryingmentioning
confidence: 99%
“…Air frying circulates hot air uniformly around the food instead of immersing it in hot oil and also reduces the fat contents in the fried food. Thus, the product is progressively dehydrated at a fixed frying temperature of 180 °C, while the crisp characteristic appears on the fried products with minimum variations in food quality (Andrés and others ; Heredia and others ; Sansano and others ). Air fryers are available on the market as an alternative to fry foods without oil, and are considered a convenient method of cooking; however, there are no studies regarding degradation of lipids by this thermal process.…”
Section: Introductionmentioning
confidence: 99%
“…O conhecimento do mecanismo de formação da acrilamida é essencial para reduzir seus níveis em alimentos, pois esta substância é um composto mutagênico e potencial carcinógeno (CHENG et al, 2014;HEREDIA et al, 2014;XU et al, 2014). Embora alimentos ricos em carboidrato sejam comumente pesquisados para determinação de acrilamida, alimentos ricos em proteína, como carnes cozidas em temperaturas elevadas, também contém este contaminante (KAPLAN et al, 2009).…”
Section: Lista De Tabelasunclassified
“…Os valores elevados de b* na carne empanada e frita até 90 ⁰C indicam cor amarela intensa, desejável para alimentos fritos (HEREDIA et al, 2014). A diminuição da coordenada b* para carne grelhada / frita a 100 ⁰C e também para a assada a 300 ⁰C mostra menor predominância do componente amarelo e uma proporção maior do componente azul, o que também pode ser visualizado pelos valores diminuídos de Chroma (C) nos tratamentos grelhado e empanado e frito.…”
Section: Análise Instrumental De Cor Da Carne Bovina Cozidaunclassified
See 1 more Smart Citation